Decolonising global health research: Shifting power for transformative change - Kumar, R.; Khosla, R.; McCoy, D. (Public Library of Science, 2024)
Recent debates on decolonizing global health have spurred interest in addressing the power asymmetries and knowledge hierarchies that sustain colonial ideas and relationships in global health research. This paper applies three intersecting dimensions of colonialism (colonialism within global health; colonisation of global health; and colonialism through global health) to develop a broader and more structural understanding of the policies and actions needed to decolonise global health research. It argues that existing guidelines and checklists designed to make global health research more equitable do not adequately address the underlying power asymmetries and biases that prevail across the global health research ecosystem. Beyond encouraging fairer partnerships within individual research projects, this paper calls for more emphasis on shifting the balance of decision-making power, redistributing resources, and holding research funders and other power-holders accountable to the places and peoples involved in and impacted by global health research.